Facile synthesis of hydrochar-supported catalysts from glucose and its catalytic activity towards the production of functional amines - Xiuzheng Zhuang; Jianguo Liu; Longlong Ma (Green Energy & Environment, 2023)
Since the utilization of abundant biomass to develop advanced materials has become an utmost priority in recent years, we developed two sustainable routes (i.e., the impregnation method and the one-pot synthesis) to prepare the hydrochar-supported catalysts and tested its catalytic performance on the reductive amination. Several techniques, such as TEM, XRD and XPS, were adopted to characterize the structural and catalytic features of samples. Results indicated that the impregnation method favors the formation of outer-sphere surface complexes with porous structure as well as well-distributed metallic nanoparticles, while the one-pot synthesis tends to form the inner-sphere surface complexes with relatively smooth appearance and amorphous metals. This difference explains the better activity of catalysts prepared by the impregnation method which can selectively convert benzaldehyde to benzylamine with an excellent yield of 93.7% under the optimal reaction conditions; in contrast, the catalyst prepared by the one-pot synthesis only exhibits a low selectivity near to zero. Furthermore, the gram-scale test catalyzed by the same catalysts exhibits a similar yield of benzylamine in comparison to its smaller scale, which is comparable to the previously reported heterogeneous noble-based catalysts. More surprisingly, the prepared catalysts can be expediently recycled by a magnetic bar and remain the satisfying catalytic activity after reusing up to five times. In conclusion, these developed catalysts enable the synthesis of functional amines with excellent selectivity and carbon balance, proving cost-effective and sustainable access to the wide application of reductive amination.